Emission of carbon monoxide, total hydrocarbons and particulate matter during wood combustion in a stove operating under distinct conditions - Vicente, E. D.
Wood combustion experiments were carried out to determine the effect of ignition technique, biomass load and cleavage, as well as secondary air supply, on carbon monoxide (CO), total hydrocarbon (THC), particulate matter (PM10) and particle number emissions fromawoodstove.Wood fromtwo typical tree species in the Iberian Peninsula was selected: pine (Pinus pinaster) and beech (Fagus sylvatica). The highest CO and total hydrocarbon emission factors (EFs) were observed, respectively, for pine and beech, for high and low fuel loads. The highest PM10 EFwas recorded for the operationwith lowloads for bothwoods. Secondary air supply produced the lowest PM10 emission factors. The top ignition can decrease the PM10 EF to less than halfwhen compared with the common technique of lighting from the bottom. The lowest particle number emission factors were observed when operating with high loads of split beech logs and when using secondary air supply during the combustion of pine. Regarding particle number distributions, the highest geometric mean diameter (Dg), for both woods, were observed when operating with high loads (with split and non-split wood).